(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: This study was carried out to compare the mean pain score in patients of medial compartmental osteoarthritis of knee before and after proximal fibular osteotomy (PFO). Methodology: This single group quasi experimental study of thirty patients was carried out in the Orthopaedic department. The patients of primary knee osteoarthritis involving only medial compartment for 3 months to 2 years with Kellgren and Lawrence grade 2-3 were included in the study. Visual analog scale was used for pain assessment before and after PFO on the day before the surgery and again after two months of surgery. Paired sample t-test was used to compare them. Results: The patients mean age was 49.63±6.68 years (range 38 – 59 years). There were 19 (63.33%) female and 11 (36.67%) male patients. Mean pre-PFO pain score was 7.30±1.15 (range 5-10). Mean post-PFO pain score was 2.87±0.82 (range 1-4). There were 14 (46.67%) patients with right side involvement and 16 (53.33%) were with left side involvement. Diabetes was diagnosed in 07 (23.33%), hypertension was found in 09 (30.00%) patients. Eleven (36.67%) out of 30 patients were smokers. In age group of 38-50 years, mean pre-PFO pain score was 7.14±1.03 and post-PFO pain score was 2.71±0.73 (p<0.001). In patients having age 51-59 years, mean pre-PFO pain score was 7.44±1.26 and post-PFO pain score was 3.00±0.89 (p<0.001). In male patients, mean pre-PFO pain score was 7.36±1.21 and post-PFO pain score was 2.91±0.83 (p<0.001). In female patients, mean pre-PFO pain score was 7.26±1.15 and post-PFO pain score was 2.84±0.83 (p<0.001). Conclusion: Proximal fibular osteotomy is an effective method for relief of pain with significant reduction in VAS score and thus functional regain with little or no complications in Kellgren and Lawrence grade 2-3 primary knee osteoarthritis.